The Role of Environmental Law Education for Sustainable Development - Audzei, Hanna (European Journal of Sustainable Development, 2019)
National imperative of sustainable development is a strategy that combines into one social, economic and environmental policies. First of all the environmental legal education should aim to prepare people for life in an innovative type of society. To achieve this goal of environmental and legal education we should be reoriented to form a human ecological and legal culture and eco-innovative type of legal thinking and a willingness to innovative type of environmental and legal action. The successful solution of this and other challenges requires science foundation, including environmental law science. Keywords: law, environmental legal education, sustainable development, environmental safety, ecology, responsibility, ecological culture, legislation